New Perspective of Origanum vulgare L. and Satureja montana L. Essential Oils as Bovine Mastitis Treatment Alternatives - Zorana Kovačević; Nebojša Kladar; Ivana Čabarkapa; Miodrag Radinović; Milan Maletić; Mihajlo Erdeljan; Biljana Božin (MDPI AG, 2021)
Mastitis represents a heavy burden for the dairy sector worldwide with high economic and animal welfare impact. Antibiotic treatment is an important component of mastitis control programs. However, emergence and transfer of antimicrobial-resistant (AMR) bacteria is becoming a growing concern. Therefore, the development of novel agents is required for prevention and treatment of mastitis. Hence, our aim was to assess the antibacterial properties of two essential oils (EOs) obtained from oregano (Origanum vulgare L., Lamiaceae) and mountain savory (Satureja montana L., Lamiaceae) against mastitis-associated bacteria in Serbia. The chemical composition and antioxidant potential of these EOs were also evaluated. The present study was conducted on strains derived from aseptic milk samples collected from Holstein-Friesian cows with clinical or subclinical mastitis, during the morning milking. Clinical mastitis was assessed by clinical examination, while subclinical mastitis was confirmed using somatic cell count in the milk samples. The microdilution method was used to determine the antibacterial activity, while antioxidant potential of the EOs was evaluated in several in vitro assays. The values of minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs) were used to quantitatively measure the antibacterial activity of each EO. MIC/MBC ranged from 0.78/6.25 and 0.39/0.78 mg/mL for oregano and mountain savory, respectively. A total of 25 compounds were identified in the oregano EO, while 47 were identified in winter savory EO, among which aromatic oxygenated monoterpenes were the most abundant compounds. The tested EOs have shown promising antimicrobial activity and could be considered as one of the treatment approaches in mastitis-affected cows.